Effects of Aerosols and Climate Properties on Solar Radiation amount Falling on Horizontal Surface at Kerbala City - Rasool Ramadhan Attab , (University of Thi-Qar Journal of Science, 2020)
In this paper a mathematical description for solar radiance falling on the horizontal surface on Iraq (kerbala city) was investigated and compared with real measurements, the city having the position of (E,32° 37′ 0″ N, 44° 1′ 59.99″ ) 32.61, 44.03, the solar radiation as a clean energy source suffering many process that reduce its efficiency to providing many applications with a free source of energy this process mainly due to the absorption, scattering and diffraction of electromagnetic light wave, the results show that there is a major absorption by aerosols, clouds and atmospheric gases produced significantly by CO2, CH4,N2O,CO and O2 due to their size about 10-4 to 10 µm and its concentration in atmosphere, a main relation between the solar harvesting energy and geometrical, data for the position and day time for the sun on site of study, a climate data for the year 2018 used, finally a good identical among theoretical, real, and results obtained from other solar irradiance models.